P05.44 Single-cell transcriptomic analysis of microglia/macrophages in Glioblastoma. (19th September 2018) - Michelucci, A; Golebiewska, A; Pires-Afonso, Y; Poovathingal, S K; Oudin, A; Balling, R; Skupin, A; Niclou, S P
Abstract: Background: Glioblastoma (GBM) is characterized by prominent genetic and histopathological heterogeneity. A major contributing factor to GBM development and progression is its ability to evade the immune system. Neoplastic cells are known to release factors that recruit resident microglia, macrophages and other peripheral immune cells and transform them into tumour-supportive cells. It remains unclear how and when the tumour-promoting characteristics of the microglia/macrophage population (MM) are established and how they differ in different regions of the tumour, e.g. infiltrative areas versus tumour core. Methods: MM behaviour was analysed in established patient-derived orthotopic xenografts (PDOX) that represent different stages of tumour progression and recapitulate inter- and intra-tumour heterogeneity observed in patients. 'Invasive' tumours present an apparent normal brain vasculature while 'angiogenic' phenotypes are more circumscribed, display necrotic areas and microvascular proliferation. We applied multicolour flow cytometry combined with immunohistochemistry and single cell RNA-Seq using the DropSeq method to study MM characteristics. Results: We found that MMs display different morphologies and activation states depending on the histopathological features of GBM, with a prominent accumulation in and around the tumour core. Taking advantage of high-throughput single-cell sequencing, we elucidated specific MM transcriptional profiles associated with invasive and angiogenic tumours, thus revealing high immune cell heterogeneity related to specific tumour compartments. Conclusions: Single cell-Seq allows for an unbiased, surface marker-free approach to decipher MM transcriptional signatures at the single-cell level and enabled the elucidation of MM subtypes correlating to temporal and spatial heterogeneity in GBM. These analyses provide a better understanding of pro- and anti-tumourigenic MM phenotypes which may pave the way for therapeutic exploitation.